Comparation Between Station Management and Water Source on the Quality of Refill Drinking Water in Surabaya - Nida'an Khafiya; Linda Dewanti; Wiwin Retnowati (Humanistic Network for Science and Technology (HNST), 2020)
Drinking water is both a basic human need and a strong determinant of health. In Indonesia, there are drinking water refill stations (DWRS) which conveniently offer refill drinking water at affordable price. This study aims to determine whether station management amd raw water source influence the quality of drinking water. This cross-sectional study used primary data from questionnaires filled by DWRS owners and secondary data about the quality of refill drinking water from the Surabaya City Health Department. Data was then analyzed by using Chi-Square and Mann-Whitney tests. From 33 registered DWRSs, only 18 stations fulfilled all quality standards of drinking water. Some DWRSs failed to pass microbiological (n=13) and chemical (n=2) standards. All DWRS passed the physical standard. There was no significant difference found in duration of operation (pmicro = 0.956, pchemical = 0.382), production capacity (pmicro = 0.384; pchemical = 0.495). There was no significant difference found in terms of station management and raw water sources on the quality of refill drinking water. Keywords: drinking water refill station (DWRS); duration of operation; production capacity; raw water source